2020
DOI: 10.7717/peerj.9482
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram data as a tool for decision-making in COVID-19 management: applications to resource scarcity scenarios

Abstract: Background COVID-19 pandemics has challenged emergency response systems worldwide, with widespread reports of essential services breakdown and collapse of health care structure. A critical element involves essential workforce management since current protocols recommend release from duty for symptomatic individuals, including essential personnel. Testing capacity is also problematic in several countries, where diagnosis demand outnumbers available local testing capac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Further, this work presents some major limitations affecting replicability and generalizability, as the authors do not provide any information regarding how the values of the considered features were measured (analytical instruments, analytical principle, and units of measurement). Avila et al [33] used the same dataset considered in [32] to develop a Bayesian model, reporting 76.7% sensitivity and specificity. Notably, the authors report a number of complete instances (510) which is different from that reported in [32].…”
Section: Datasetmentioning
confidence: 99%
“…Further, this work presents some major limitations affecting replicability and generalizability, as the authors do not provide any information regarding how the values of the considered features were measured (analytical instruments, analytical principle, and units of measurement). Avila et al [33] used the same dataset considered in [32] to develop a Bayesian model, reporting 76.7% sensitivity and specificity. Notably, the authors report a number of complete instances (510) which is different from that reported in [32].…”
Section: Datasetmentioning
confidence: 99%
“…The potential applications of ML for COVID-19 have been previously described [14,[16][17][18][19][20][21][22][23][24][25][26]. The details are summarized in Table 1.…”
Section: Machine Learning-based Diagnostic Applicationsmentioning
confidence: 99%
“…We evaluate and compare our proposed approach of lifelong learning and assessment against standard ML approaches on a large-scale data set. This data set comprises 127,115 samples after pre-processing and merging, which exceeds the data set size of many small scale studies [18][19][20][21][22]32 by far. Our data set comprises pre-pandemic negative samples and pandemic negative and positive samples spanning over multiple different departments of the Kepler University Hospital, Linz.…”
Section: Degrading Of Predictive Performance Over Timementioning
confidence: 99%
“…COVID-19 and the patient's prognosis can be predicted from chest CT-scans, X-rays [11][12][13][14] or sound recordings of coughs or breathing [15][16][17] . Furthermore, it has been shown that ML models based on blood tests are capable of detecting COVID-19 infection [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and predicting other outcomes, such as survival or admission to an intensive care unit [33][34][35][36][37][38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation